Efforts to Revitalize the Dieng Critical Slope trough Community Empowerment: Case Tambi Coffee - Fajar Julian Santosa (Prospect Publishing, 2022)
Dieng Plateau is a protected area whose main function is to protect the preservation of the function of natural resources, artificial resources, as well as cultural and historical values of the nation. Forest damage in the Dieng Plateau has reached 50 to 60%. The conversion of forest functions to land for seasonal crops, especially potatoes has damaged the forest function area as a protected forest. The problem that is still the biggest challenge in efforts to restore Dieng as a protected area is the rehabilitation of critical land in community-owned land areas. Widespread land degradation occurs due to potato cultivation activities, the impact is that during the rainy season landslides occur in many residential points and along roads, floods that occur due to disruption of watersheds by landslides, and drought during the dry season. This research was conducted using qualitative methods with purposive selection of research locations. The research location is in Tambi Village, Wonosobo Regency, which is a conservation area through coffee cultivation. Observations and in-depth interviews were conducted. The results of this study indicate that community empowerment in Tambi Village is an important factor in efforts to revitalize the critical slopes of Dieng. This revitalization effort has been carried out by Bapak Romadhon for the last 12 years together with the surrounding community by planting coffee plants. Behind the success that has been achieved, there are many influencing factors, both external and internal. Many coffee farmers feel the benefits of growing coffee. The community began to realize that the activities they were doing so far were damaging the environment. Community empowerment and participation is a very important step for the recovery of critical slopes due to exploitation activities.